Next generation sequencing of Y-STRs in father-son pairs and comparison with traditional capillary electrophoresis - Steffi Bredemeyer; Lutz Roewer; Sascha Willuweit (Oxford University Press, 2021)
To evaluate the promising advantages of massively parallel sequencing (MPS) in our casework, we analysed a total of 33 Y-chromosomal short tandem repeats (Y-STRs) with traditional capillary electrophoresis (CE) and 25 Y-STRs using the newer MPS technology. We studied the outcome of both technologies in 64 father-son pairs using stock and custom-designed kits. Current MPS technology confirmed the 13 mutational events observed with CE and improved our understanding of the complex nature of STR mutations. By detecting isometric sequence variants between unrelated males, we show that sequencing Y-STRs using MPS can boost discrimination power.